Deep stretch of polyethylene by transverse loading: Finite element simulation to characterize the influence of indenter size and loading speed on the stress development and distribution. Issue 9 (3rd August 2021) - Ebrahimian, Azadeh; Ward, Patrick; Jar, P.‐Y. Ben
Abstract: Deep stretching has been found to decrease the cracking resistance of polyethylene (PE) in an aggressive environment. This idea has been adopted for developing a test method that uses indentation loading to generate a deep stretch of a PE plate so that time for crack generation is shortened. Work presented is to use finite element (FE) modeling to investigate the influence of indenter size and loading speed on the efficacy of the test method. Mechanical testing was carried out using cylindrical indenters of 7 and 13 mm in diameter on a plate that is supported so that only a 15‐mm diameter area can be stretched. Test results were used to calibrate material input data for the FE modeling and to establish the stress development and distribution during the deep stretch process. FE modeling considered three types of material input, one purely based on elastic–plastic deformation and the other two considering creep or damage during the deep stretch. All FE modellings suggest that the 13‐mm indenter is more effective than the 7‐mm indenter in introducing a monotonic total stress increase during the deep stretch, and thus the study concludes that the former should be used to introduce the deep stretch. Abstract : This work used finite element simulation, calibrated by experimental test results, to examine the influence of indenter size and loading speed on the disintegration of crystalline phase in polyethylene.